Feasibility of Additively Manufactured Tunable Liquid Crystal Loaded Dielectric Waveguides - Tesmer, Henning; Gold, Gerald; Bachbauer, Felix; Polat, Ersin; Sippel, Mark; Jakoby, Rolf; Vossiek, Martin; Maune, Holger (IEEE Microwave and Wireless Components Letters, 2021)
This paper investigates the feasibility of the combination of additive manufacturing and liquid crystal (LC) loaded dielectric waveguides (DWGs) at W-band (75 to 110 GHz). The waveguide is extruded such that it has a cavity in its center, used for LC hosting. Reproducible cross sections are achieved along the DWG and high agreement in differential phase shift and figure-of-merit (FoM) are obtained when the DWG is biased electrically or magnetically. De-embedding the structure shows attenuation constants between 0.12 dB/cm to 0.33 dB/cm which lead to a high FoM in the range of 100 °/dB to 160 °/dB. According to simulations higher values are obtainable if larger LC cavities are realized.<br
Keywords: Liquid Crystal; Additive Manufacturing; Phase Shifter; Dielectric Waveguide; mm-Wave Components; Reconfigurable Devices